Recurrent acute idiopathic pericarditis: rheumatologic therapy, autoantibodies and long term outcome - D. Spodick; A. Caforio; P. Coppini; M. Bosetti; Y. Adler; A. Brucato; G. Brambilla; B. Canesi (PAGEPress Publications, 2011)
Objective: To evaluate therapy and rheumatologic aspects of recurrent acute idiopathic pericarditis (RAIP). Methods: We studied 46 patients. We used non-steroidal anti-inflammatory drugs (NSAIDs) at high dosage. We did not start corticosteroid: if already started, we planned a very slow tapering; 37 patients (80.4%) were treated with colchicines. We also assessed the frequency of ANA, anti-SSA and Rheumatoid factor. Results:With our protocol recurrences dropped from 0.46 to 0.03 attacks/patient/month (p<0.00001) within 12 months and remained at the same level (0.024) till the end of the follow-up (mean 8 years). In the 37 patients treated with colchicine recurrences dropped from 0.5 to 0.03 (p<0.0001) within 12 months, and in 9 patients not given colchicine from 0.27 to 0.045 (p<0.005).When colchicine was used the decrease was significantly higher (0.47 vs 0.23) (p<0.001). In 27 (58.7%) patients ANA were positive at a titre >1/80, in 7 (15.2%) >1/160. Rheumatoid factor was positive in 7 (15.2%) and anti-SSA in 4 (8.7%). During the follow-up 4 (8.7%) new diagnosis of Sjogren and 1 (2.2%) of Rheumatoid Arthritis were made. Conclusion: NSAIDs at high dosage, slow tapering of corticosteroid and colchicine are very effective in RAIP. The improvement is more dramatic in colchicine treated patients, but also other patients can achieve good control of the disease. The finding of ANA, anti-SSA and the new rheumatological diagnoses support the involvement of autoimmunity.